Multi-carrier communication systems with examples in MATLAB : a new perspective - Hassan, Emad S. (CRC Press, an imprint of the Taylor and Francis Group, 2015)
Detailing the advantages and limitations of multi-carrier communication, this book proposes possible solutions for these limitations. Multi-Carrier Communication Systems with Examples in MATLABr: A New Perspective addresses the two primary drawbacks of orthogonal frequency division multiplexing (OFDM) communication systems: the high sensitivity to carrier frequency offsets and phase noise, and the high peak-to-average power ratio (PAPR) of the transmitted signals. Presenting a new interleaving scheme for multicarrier communication, the book starts with a detailed overview of multi-carrier systems such as OFDM, multi-carrier code division multiple access (MC-CDMA), and single-carrier frequency division multiple access (SC-FDMA) systems. From there, it proposes a new way to deal with the frequency-selective fading channel: the single-carrier with frequency domain equalization (SC-FDE) scheme. The second part of the book examines the performance of the continuous phase modulation (CPM)-based OFDM (CPM-OFDM) system. It proposes a CPM-based single-carrier frequency domain equalization (CPM-SC-FDE) structure for broadband wireless communication systems. In the third part of the book, the author proposes a chaotic interleaving scheme for both CPM-OFDM and the CPM-SC-FDE systems. A comparison between the proposed chaotic interleaving and the conventional block interleaving is also performed in this part. The final part of the book presents efficient image transmission techniques over multi-carrier systems such as OFDM, MC-CDMA, and SC-FDMA. It details a new approach for efficient image transmission over OFDM and MC-CDMA systems using chaotic interleaving that transmits images over wireless channels efficiently. The book studies the performance of discrete cosine transform-based single-carrier frequency division multiple access (DCT-SC-FDMA) with image transmission. It also proposes a CPM-based DCT-SC-FDMA structure for efficient image transmission. The book includes MATLABr simulations along with MATLAB code so you can practice carrying out your own extensive simulations.